2011
DOI: 10.1021/je2002072
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Determination of Quaternary and Ternary Isobaric Vapor–Liquid–Liquid Equilibrium and Vapor–Liquid Equilibrium for the Systems Water–Ethanol–Hexane–Toluene and Water–Hexane–Toluene at 101.3 kPa

Abstract: Experimental isobaric vapor–liquid–liquid and vapor–liquid equilibrium (VLLE and VLE) data for the ternary system water (1)–hexane (2)–toluene (3) and the quaternary system water (1)–ethanol (2)–hexane (3)–toluene (4) were measured at 101.3 kPa. An all-glass, dynamic recirculating still equipped with an ultrasonic homogenizer was used to determine the VLLE. The results obtained show that the system does not present quaternary azeotropes. The point-by-point method by Wisniak for testing the thermodynamic consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…First, VLLE calculations were compared to the measurements of Pequenín et al The systems were water–toluene–cyclohexane, water–toluene–hexane, and water–cyclohexane–heptane . The values of HC–HC k ij were determined from SRK correlation of the VLE experimental data: 0.0221 for toluene–cyclohexane, 0.0117 for toluene–hexane, , and −0.0042 for cyclohexane–heptane .…”
Section: Predictionsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, VLLE calculations were compared to the measurements of Pequenín et al The systems were water–toluene–cyclohexane, water–toluene–hexane, and water–cyclohexane–heptane . The values of HC–HC k ij were determined from SRK correlation of the VLE experimental data: 0.0221 for toluene–cyclohexane, 0.0117 for toluene–hexane, , and −0.0042 for cyclohexane–heptane .…”
Section: Predictionsmentioning
confidence: 99%
“…Comparison among predicted and measured vapor-phase composition of the systems water–toluene–cyclohexane (black), water–toluene–hexane (red), and water–cyclohexane–heptane (blue). Diamonds: water; squares: toluene; circles: cyclohexane; crosses: hexane, triangles: heptane.…”
Section: Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem can be solved quickly using a spreadsheet and by changing the solution temperature until Equation 26is satisfied. Sometimes, the temperature of the solution is known and the total pressure needs to be calculated, which is a straightforward calculation from Equation (26). This way, there is no need to use the nonlinear solvers to find the temperature.…”
Section: Ideal Solution Mixtures: Vle Phase Behaviormentioning
confidence: 99%
“…The higher the purity of the alcohol being used as additive, the better the performance of the fuel. It was found that the addition of glycols to the mixture containing alcohols and water can improve the separation processes and utilize less energy to perform the process [25,26]. The experimental data containing the ternary system of ethylene glycol-water-ethanol and the performance of separation by varying the glycol concentration were performed by Kamihama et al [27].…”
Section: Vle Study Of a Ternary Systemmentioning
confidence: 99%